Narratives and multiperspectivity in Dutch secondary school history textbooks - Kropman, Marc (Journal of educational media, memory, and society, 2020)
School history textbooks provide an important source of information for learners of history. Textbook narratives of a nation's past often present a limited frame of reference, which impedes the aim of teaching history from multiple perspectives. This article examines the representation of the Dutch Revolt in two Dutch and two Flemish history textbooks. By taking sentences as our unit of analysis, we analyzed narrative elements and metaphors, which informed us about the level of multiperspectivity in these narratives. We found that Dutch textbooks, in contrast to Flemish textbooks, create their emplotment of the narrative of the Dutch Revolt by focusing on the first ten years of the conflict and mostly lack multiperspectivity. We hope that the insights generated by this analysis may inform textbook authors who seek to do justice to multiple perspectives.